HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI PETANI DENGAN PENDAPATAN USAHATANI SEMANGKA (Suatu Kasus Di Desa Cikadu Kecamatan Cikalong Kabupaten Tasikmalaya) - Fitri Awaliyah; Ane Novianty (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2022)
The purpose of this study was to analyze the socio-economic relationship of farmers consisting of age, farming experience and land area to watermelon farming income. The research was conducted in Cikadu Village, Cikalong District, Tasikmalaya Regency. This type of research is an associative research with a quantitative approach. The sampling technique in this research uses the census technique, by taking 10 farmers who continuously cultivate watermelons in one year. The data analysis technique used Pearson correlation analysis using SPSS software. The results showed that age had a strong relationship with income. But the experience of farming in the case of this study has a negative relationship with the level of income. Meanwhile, land area has a very strong relationship with the income level of watermelon farmers.